2001
DOI: 10.1128/jb.183.2.461-467.2001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen- and Growth Rate-Dependent Regulation of Escherichia coli Fumarase (FumA, FumB, and FumC) Activity

Abstract: Escherichia coli contains three biochemically distinct fumarases which catalyze the interconversion of fumarate to L-malate in the tricarboxylic acid cycle. Batch culture studies indicated that fumarase activities varied according to carbon substrate and cell doubling time. Growth rate control of fumarase activities in the wild type and mutants was demonstrated in continuous culture; FumA and FumC activities were induced fourto fivefold when the cell growth rate (k) was lowered from 1.2/h to 0.24/h at 1 and 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
64
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 40 publications
4
64
0
Order By: Relevance
“…However, our study has shown that the glucose supplement did not make a significant difference in the growth rates when E. coli was growing in LB medium. These findings are consistent with those of the previous study showing that the growth rate of E. coli is barely affected when glucose is added to LB media (31). In this study, the doubling times were similar: 41 min when wild-type E. coli was grown in LB and 37 min when it was grown in LB supplemented with glucose (40 mM).…”
Section: Discussionsupporting
confidence: 82%
“…However, our study has shown that the glucose supplement did not make a significant difference in the growth rates when E. coli was growing in LB medium. These findings are consistent with those of the previous study showing that the growth rate of E. coli is barely affected when glucose is added to LB media (31). In this study, the doubling times were similar: 41 min when wild-type E. coli was grown in LB and 37 min when it was grown in LB supplemented with glucose (40 mM).…”
Section: Discussionsupporting
confidence: 82%
“…Fumarase A is the major active E. coli fumarase under microaerophilic conditions (49). E. coli fumarase B has a higher affinity for malate than for fumarate and appears to operate under anaerobic conditions to generate fumarate from malate (49,55). Fumarase C is highly active under aerobic growth conditions (49).…”
Section: Resultsmentioning
confidence: 99%
“…There are three fumarases in Escherichia coli, fumarase A, fumarase B, and fumarase C, encoded by fumA, fumB, and fumC, respectively (2, 31, 54). Fumarase A is the major active E. coli fumarase under microaerophilic conditions (49). E. coli fumarase B has a higher affinity for malate than for fumarate and appears to operate under anaerobic conditions to generate fumarate from malate (49,55).…”
Section: Resultsmentioning
confidence: 99%
“…Fumarate hydratase A, the component of the Kreb's cycle (citric acid cycle) that converts fumarate to malate, is encoded by fumA (46). The citric acid cycle is one of the three metabolic pathways of cellular respiration and is necessary for fuel catabolism and ATP production.…”
Section: Discussionmentioning
confidence: 99%